Budaya Leles Orang Manggarai Sebagai Suatu Fenomena Sosial Dalam Terang Filsafat Metafisika Heidegger - Raimundus Awur (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
This research focuses on the (social) cultural phenomenon of Leles Orang Manggarai in the context of social change driven by the influence of modern technology. Current conditions indicate a decline in unity and cooperation within this culture. The study employs a qualitative approach with literature review, interviews, and Heideggerian philosophical analysis to elucidate the changes in this cooperative culture. Literature review and interviews reveal the dynamics of Leles culture that has undergone transformation due to interactions with modern technology, resulting in a decline in the previously strong values of unity and cooperation in Manggarai society. In the philosophical context of Heidegger, the research examines the metaphysical implications for the changed Leles culture. The qualitative findings provide insights into how modern technology has influenced culture and social values, and how Heideggerian thought can be applied to contemplate societal changes. This research contributes significantly to understanding the impact of technology on culture and cooperation in Manggarai society. It is essential to underline that this study does not aim to examine the entire Manggarai society or address social phenomena universally, like sociological theories. Instead, it emphasizes the social benefits of Leles culture, presenting social phenomena as a reflective framework in this context.